Meliosma mexicana (Sabiaceae), a new species from the Sierra Madre Oriental of Mexico - W. Steinmann, Victor (Instituto de Ecología, A.C., 2007)
Meliosma mexicana (Sabiaceae) is described as a new species. It occurs in the Sierra Madre Oriental of Mexico in the states of Querétaro and Tamaulipas, growing primarily in cloud forest and humid pine-oak forest at elevations of 800 to 1900 m. It belongs to subg. Meliosma sect. Lorenzanea. It is most similar to M. dentata, which it apparently replaces in northeastern Mexico. Meliosma mexicana is distinguished from M. dentata in having essentially entire leaves, stipitate glandular trichomes that vary from red to blackish, and subglobose fruits 0.6 to 0.7(0.8) cm long.